PEMAHAMAN AKUNTANSI ZAKAT DAN TINGKAT RELIGIUSITAS TERHADAP KESADARAN MEMBAYAR ZAKAT PADA PELAKU UKM MUSLIM - Sri Wahyuni Br Ginting; Widia Astuty; Irfan (Jurnal At-Tabayyun, 2020)
The purpose of this research is to analyze, test and find out whether there is an influence between understanding zakat accounting and the level of religiosity on the awareness of paying zakat on business actors for their zakat trading. The decision of the muzakki to pay zakat is very interesting to trace, which is seen from the side of faith that underlies the emergence of awareness to issue zakat, namely the understanding of the zakat fiqh, besides that the practice and promise that Allah has explained in the Al Quran is a guideline that zakat is assets that must be issued. In terms of accounting, it is also related to accounting behavior and calculations as well as the decision to issue zakat, the correct calculation concept is needed in terms of calculating trade zakat, because there are still many business actors who do not understand the basis for calculating zakat. This research was conducted by taking samples of 55 respondents, namely Muslim UKM players in Medan City. This study uses a questionnaire as a data collection tool. Structural Equation Modeling-Partial Least Squares (SEM-PLS) which is used to analyze data, so that it can show the results of this study where there is no effect of understanding zakat accounting on the awareness of paying zakat, but there is a considerable influence on the level of religiosity on the awareness of the actors. businesses to want to spend their trade zakat